2022
DOI: 10.1659/mrd-journal-d-21-00061.1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Revitalization of Local Ecological Knowledge in Four Schools in Yasin Valley, North Pakistan

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Our research group has found some important strategies for revitalizing LEK in schools, which could provide a foundation for promoting these practices in other mountain territories. For example, together with the local community in the Yasin Valley of Pakistan, we identified some approaches that could help in the revitalization of LEK among young community members, such as study trips, traditional food day celebrations, developing WFP herbaria, art competitions, and the introduction of "food scouting" (ethnobiology-centered documentation of threatened local foods) into school curricula [52].…”
Section: Revitalization Of Local Plant Knowledgementioning
confidence: 99%
“…Our research group has found some important strategies for revitalizing LEK in schools, which could provide a foundation for promoting these practices in other mountain territories. For example, together with the local community in the Yasin Valley of Pakistan, we identified some approaches that could help in the revitalization of LEK among young community members, such as study trips, traditional food day celebrations, developing WFP herbaria, art competitions, and the introduction of "food scouting" (ethnobiology-centered documentation of threatened local foods) into school curricula [52].…”
Section: Revitalization Of Local Plant Knowledgementioning
confidence: 99%
“…The WEPs potential of the area may be transformed to for agricultural diversi cation. This practice would be effective for easy survival, economic development and food security of the arid province (Aziz et al, 2022). The remote communities are traditional and have limited socio-economical perceptions to change their life routines.…”
Section: Part(s) Used and Marketing Of Wepsmentioning
confidence: 99%
“…A signi cant volume of traditional knowledge associated with food ethnobotany exists in the province and presented by all ethnic communities. But it is being limited to the aged people and cause low intergenerational transmission as reported in various studies (Aziz et al, 2022;Bibi et al, 2022). In the marginalized human societies the utilization and business of WEPs are perceived as laborious practice with low pro t (ARSHAD et al, 2022).…”
Section: Transmission and Fragmentation Of Traditional Knowledgementioning
confidence: 99%
“…The classical ethnobotanical approach examines the reasons for changes in plant use. Numerous factors have been identified, including changes in the environment (Fernández‐Llamazares et al, 2015; Gómez‐Baggethun et al, 2013), climate (García‐del‐Amo et al, 2023), lifestyle (Cuerrier et al, 2019), economy (Mattalia, Sõukand, et al, 2021; Reyes‐García et al, 2007), policies (Ceuterick et al, 2008; Mattalia et al, 2023), education (Aziz et al, 2022; Nankaya et al, 2019), and so forth. Over time, long‐term changes in the use of wild food plants have been studied in Europe, and a decrease in usage has also been noted (Łuczaj, 2010; Łuczaj & Dolina, 2015) including on the islands (Dolina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%